From Warranty Voids to Uprising Advocacy: Human Action and the Perceived Moral Patiency of Social Robots - Banks, Jaime (Frontiers in Robotics and AI, 2021)
Moral standing can be understood along two dimensions: moral agency (capacities to be and do good [or bad]) and moral patiency (extents to which entities are objects of moral concern), where the latter especially has implications for how humans accept or reject machine agents into human social spheres. As there is currently limited understanding of how people innately understand and imagine the moral patiency of social robots, this study inductively explores key themes in how robots may be subject to humans’ (im)moral action across 12 valenced foundations in the moral matrix: care/harm, fairness/unfairness, loyalty/betrayal, authority/subversion, purity/degradation, liberty/oppression. Findings indicate that people can imagine clear dynamics by which anthropomorphic, zoomorphic, and mechanomorphic robots may benefit and suffer at the hands of humans (e.g., affirmations of personhood, compromising bodily integrity, veneration as gods, corruption by physical or information interventions). Patterns across the matrix are interpreted to suggest that moral patiency may be a function of whether people diminish or uphold the ontological boundary between humans and machines, though even moral upholdings bare notes of utilitarianism.